Sustainability level index for a simplified comparative analysis of laminated timber and other similar elements for sustainable construction in México. - López Tenorio, Mariana (2023)
In this project, the feasibility of laminated wood beams as a sustainable construction option in comparison to traditional materials is presented. To do this, an evaluation index was developed, wich takes into account the information of content, distance, process, modulation and maintenance of each material; providing a simplified and preliminary result of the sustainability of the materials for decision making in projects. Additionally the laminated beam, solid wood beam, concrete beam and steel beam were evaluated. Confirming that wood is a more environmentally friendly material, wheter presented as a solid wood beam or laminated beam.